2018
DOI: 10.3390/ijms19092612
|View full text |Cite
|
Sign up to set email alerts
|

Successful Green Synthesis of Gold Nanoparticles using a Corchorus olitorius Extract and Their Antiproliferative Effect in Cancer Cells

Abstract: A facile bottom-up “green” synthetic route of gold nanoparticles (Au NPs) is described, using a leaf extract of the Malvaceae plant Corchorus olitorius as a reducing and stabilizing agent. The size and shape of the obtained nanoparticles were modulated by varying the amounts of the metal salt and the broth extract in the reaction medium. Only one hour was required for the complete conversion to Au NPs, suggesting that the reaction rate was higher or comparable to those of nanoparticles synthesized by chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 40 publications
(54 reference statements)
5
43
0
Order By: Relevance
“…These results exhibited significant cytotoxic and anticancer effects supported by the previous report [27]. Previous studies showed that synthesized AuNPs and stated their immense effect to inhibit the cell viability of HepG2 cell lines [26]. In the present study also informed that in agreement with this previous report.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results exhibited significant cytotoxic and anticancer effects supported by the previous report [27]. Previous studies showed that synthesized AuNPs and stated their immense effect to inhibit the cell viability of HepG2 cell lines [26]. In the present study also informed that in agreement with this previous report.…”
Section: Discussionsupporting
confidence: 92%
“…The FTIR examination of the MT-AuNPs samples has confirmed the presence of various functional groups such as alcohols and alkenes. Previous study also reported that the synthesized and characterization of Corchorus olitorius extract by using gold nanoparticles on HepG2 cell lines [26].…”
Section: Discussionmentioning
confidence: 93%
“…Liu et al [46] reported that identified the AuNPs shows the fight against cancer cells. Similarly, AuNPs synthesized from Corchorus olitorius extract show good in vitro cytotoxic assay of the biocompatible against three human cancer cell lines, such as human laryngeal cancer cell lines (Hep-2), breast cancer cell lines (MCF-7), and colon cancer cell lines (HCT-116) [1]. In previous reports synthesized the AuNPs and reported their great potential to inhibit the cell viability of bladder cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nanoparticles play a major role in the medical sector as a major tool in nanomedicine drug delivery system for cancer therapy. Gold nanoparticles (AuNPs) are used in modern medical and biology studies, as well as drug delivery, photothermal cancer therapy, chemical and biochemical sensing, imaging and catalysis [1,2]. Gold nanoparticles are widely used for medical applications such as diagnostics, therapy, prevention and hygiene [3].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of spherical gold nanoparticles (AuNPs) involves the chemical reduction of chloroauric acid (HAuCl 4 ) by using sodium borohydride (NaBH 4 ) and sodium citrate as the reducing agents, thus lowering particle size up to 2-10 and 10-40 nm, respectively [4] [5]. The "green" approach for synthesizing gold nanoparticles (AuNPs) by using natural macromolecules has been attracted growing interest over the last few decades [6] [7]. The green natural compounds were reported to favour the synthesis of well-dispersed AuNPs [8].…”
Section: Introductionmentioning
confidence: 99%